2018
DOI: 10.1002/aoc.4237
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of V5+‐doped Ag/AgCl photocatalysts with enhanced visible light photocatalytic activity

Abstract: V 5+ -doped Ag/AgCl photocatalysts were prepared via the ion exchange method. The catalysts were characterized using X-ray diffractometry, transmission electron microscopy, and energy-dispersive X-ray, X-ray photoelectron, Fourier transform infrared and ultraviolet-visible spectroscopies. The V 5+doped Ag/AgCl photocatalysts show much higher photocatalytic activities than Ag/AgCl under visible light irradiation for methyl orange (MO) decomposition.Especially, the 2.0 wt% V 5+ -doped Ag/AgCl photocatalyst shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In another work, Song and co-workers successfully doped Ag/AgCl with V 5+ ion (V–Ag/AgCl) for decomposition of MO under simulated solar light illumination . The V–Ag/AgCl photocatalyst exhibits higher photocatalytic activity and stability than bare Ag/AgCl.…”
Section: Strategies For Improving the Stability Of Semiconductor-base...mentioning
confidence: 99%
See 1 more Smart Citation
“…In another work, Song and co-workers successfully doped Ag/AgCl with V 5+ ion (V–Ag/AgCl) for decomposition of MO under simulated solar light illumination . The V–Ag/AgCl photocatalyst exhibits higher photocatalytic activity and stability than bare Ag/AgCl.…”
Section: Strategies For Improving the Stability Of Semiconductor-base...mentioning
confidence: 99%
“…In another work, Song and co-workers successfully doped Ag/AgCl with V 5+ ion (V−Ag/AgCl) for decomposition of MO under simulated solar light illumination. 138 The V−Ag/ AgCl photocatalyst exhibits higher photocatalytic activity and stability than bare Ag/AgCl. Especially, the results of MO degradation cycle experiments suggested that the activity of the optimized V−Ag/AgCl sample is maintained at 97% for five cycles, confirming the effective photocorrosion inhibition of V−Ag/AgCl.…”
Section: Strategies For Improving the Stability Of Semiconductor-base...mentioning
confidence: 99%
“…[5,[15][16][17] In particular, nano-Ag/Ag halide particles can flexibly change the range of visible light absorption by changing the morphology or reaction conditions, or can be modified by doping a promoter. [18][19][20][21][22][23][24] For instance, the compounding with graphene can accelerate the photoelectron-hole separation and enlarge specific surface area, thus largely improving the photocatalytic performance of Ag/Ag halide photocatalysts. Huang et al synthesized Ag/AgCl/TiO 2 /graphene and Ag/Ag 2 O/TiO 2 /graphene heterojunction compound photocatalysts from photoreduction and hydrothermal methods, characterized their structures and performances, and identified the optimal preparation condition by adjusting pH in the solutions.…”
Section: Introductionmentioning
confidence: 99%
“…These photocatalysts integrate the SPR of noble metals and the advantages of compound semiconductor photocatalysts . In particular, nano‐Ag/Ag halide particles can flexibly change the range of visible light absorption by changing the morphology or reaction conditions, or can be modified by doping a promoter . For instance, the compounding with graphene can accelerate the photoelectron‐hole separation and enlarge specific surface area, thus largely improving the photocatalytic performance of Ag/Ag halide photocatalysts.…”
Section: Introductionmentioning
confidence: 99%